2014
DOI: 10.1111/cen.12405
|View full text |Cite
|
Sign up to set email alerts
|

No significant difference in the prognostic value of the 5th and 7th editions of AJCC staging for differentiated thyroid cancer

Abstract: When comparing the stages of the seventh with the fifth edition of the AJCC for DTC, there was no significant difference in predicting DSS, EFS and OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
0
4
2
1
Order By: Relevance
“…The recommended version is per definition the one that has last been published (in this case version 7 16 ). Although there has been some discussion in literature whether the changes that were made from version 5-6 were right, the present study, in contrast with Vrachimis et al 24 who found no difference, affirms the correctness of these changes as they resulted in a higher predictive power both with regard to DTC-related mortality and loss of life expectancy. A further problem with the TNM system is that when used in strict accordance with its definition, not all patients can be staged.…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The recommended version is per definition the one that has last been published (in this case version 7 16 ). Although there has been some discussion in literature whether the changes that were made from version 5-6 were right, the present study, in contrast with Vrachimis et al 24 who found no difference, affirms the correctness of these changes as they resulted in a higher predictive power both with regard to DTC-related mortality and loss of life expectancy. A further problem with the TNM system is that when used in strict accordance with its definition, not all patients can be staged.…”
Section: Discussioncontrasting
confidence: 69%
“…13,14 Furthermore, the TNM system has gone through further iterations and is now in its 7th edition. 16 The newer versions of the TNM system (versions 6 and 7) come out as well 24 or better than the older ones (up to version 5). 25 Staging systems for DTC will only explain part of the total observed mortality.…”
Section: Introductionmentioning
confidence: 98%
“…32 However, it was excluded from the parameters for DTC in the AJCC 8th edition, 3 and was considered useful for T3 staging in the AJCC 7th edition. 33 In this study, 25.7% of PTCs had minimal ETE and 2.6% had macroscopic ETE, however, was not an independent predictor of recurrence/ progression. There were several limitations to this study.…”
Section: Discussioncontrasting
confidence: 56%
“…The characteristics of the patients with PTC in this study are presented in Table I. The clinical stage was classified according to the American Joint Committee on Cancer (2010, 7th edition) tumor node metastasis (TNM) classification system (36). Patients were stratified into low- and high-risk PTCs according to the age, metastasis, extension and size risk-group classification (37).…”
Section: Methodsmentioning
confidence: 99%